Endometrial preparation protocols did not impact outcomes after frozen-thaw embryo transfer for chronic endometritis treatment - Xiao Shi; Shuyi Zhang (Contraception and Reproductive Medicine)
Abstract Background Intended to investigate the potential effects of endometrial preparation procedures on the results of subsequent frozen embryo transfer (FET) cycles in infertile women with chronic endometritis (CE) following a single course of antibiotic therapy. Methods From July 2020 to December 2023, 773 infertile patients participated in a retrospective research. CD138 was immunostained in endometrial tissues taken during the proliferative phase. CE was suggested by the presence of CD138-positive cells in the stromal cells. Oral antibiotics were administered to every patient with a CE diagnosis. After one course of drug treatment, patients had endometrial preparation and frozen embryo transfers. This study compared the impact of different endometrial preparation strategies on pregnancy outcomes. Results Four regimens, hormone replacement treatment (HRT), ovulation induction, natural cycle, and gonadotrophin-releasing hormone agonist-HRT (GnRH agonist-HRT), did not significantly alter the outcome of pregnancy in patients with CE. Compared to other groups, the ovulation induction cycle group had a higher clinical pregnancy rate and embryo implantation rate. In addition, the miscarriage rate is lower compared to other populations. Patients with treated CE who received HRT, GnRH agonist-HRT, ovulation induction cycle, and natural cycle did not differ substantially (P > 0.05). Conclusion Patients with treated CE did not see any change in pregnancy outcomes as a result of endometrial preparation procedures.